Dampak Jumlah Kredit yang Dimiliki Rumah Tangga terhadap Kekerasan dalam Rumah Tangga (KDRT) pada Anak di Indonesia - Maulitfiani, Anjar; Handayani, Dwini (UI Scholars Hub, 2025)
This study examines the impact of intensity of household debt on domestic violence (DV) towards children in Indonesia. There is a positive relationship between the amount of household debt and the likelihood of domestic violence towards children based on literature review. This research uses a quantitative method with multinomial logistic regression analysis. The results of this study indicate that households with more than one household debt are correlated with an increased likelihood of both psychological and physical domestic violence towards children compared to the likelihood of no domestic violence, both before and after controlling variables added.